(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Four hundred (400) samples comprising eighty (80) samples each from five different species of Oreochromis niloticus, Bagrus bayad, Lates niloticus, Hydrocynus brevis and Synodontis vermiculatus were collected in batches using gill nets from 24th March -16th September, 2014; food and feeding habits were then assessed by analyzing the stomach content. The samples ranged in size from 525cm total length and 4.745g in weight. The stomach content analysis using frequency of occurrence method revealed that Oreochromis niloticus were herbivorous with dietary preference for plants and plant materials (47.27%), detritus (23.21%) and unidentifiable materials (6.06%), Bagrus bayad as carnivorous with dietary preference for fishes (52.17%), insects (23.57%), detritus (7.50%), Lates niloticus were also carnivorous with fishes (62.00%), fish parts (31.30%), insects (4.6%), Hydrocynus brevis proved carnivorous with dietary preference for fishes (42.16%), fish parts (17.83%), and Synodontis vermiculatus as an omnivore with dietary preference of plant materials (18.71%), fishes (12.69%), insect (12.19%) and detritus (17.48%).